Response of Fluted Pumpkin (Telfairia occidentalis Hook. F) to Wood Ash Rates in An Ultisol, Southeastern Nigeria - Orji, Janet Oliver; Ikeh, Angus Onwudiwe; Amanze, Alice Nnenna (Applied Research in Science and Technology, 2026)
Background: Fluted pumpkin is a major leafy vegetable widely cultivated and consumed in Nigeria and other rainforest ecological zones of West and Central Africa. The cultivation of this crop faces challenges due to the low soil fertility of the ultisols found in southeastern Nigeria, making it difficult for farmers in the region to achieve bumper harvests of both foliage and pods.Aims: The experiment aimed to evaluate the response of fluted pumpkin (Telfaria occidentalis Hook. F) to varying rates of wood ash application in ultisol soils. This study seeks to determine the optimal wood ash level that improves soil fertility and enhances the growth and yield of fluted pumpkin, thereby providing sustainable agricultural practices for farmers in southeastern Nigeria.Methods: The field experiment was conducted to evaluate the effect of wood ash application on growth and yield of fluted pumpkin (Telfaria occidentalis Hook. F). The experimental treatments were four wood (dried oil palm rachis) ash rates; 0, 2, 4 and 6 t/ha. The treatment was laid in a randomized complete block design, replicated four times.Results: The results showed that the application of wood ash enhanced growth and yield of fluted pumpkin. The treatment of 6t/ha wood ash produced 19.71 t/ha foliar yield. The treatment of 4t/ha produced 18.63 t/ha foliar yield. The least foliar yield, 8.81 t/ha was recorded in the control treatment. Comparing the number of pods per plant, the treatment of 6t/ha wood ash produced significant number of pods per plant; 3.60, followed by 3.43 fluted pumpkin pods per plant recorded in the treatment of 4t/ha wood ash. The least number of pods per plant; 1.12 was recorded in the control treatment. The treatment that received 6t/ha oil palm rachis ash (OPRA) produced 26.81 t/ha pod, followed by 25.01 t/ha recorded in 4t/ha wood ash rate. The least pod yield; 7.44 t/ha was recorded in the control treatment. The study revealed that application of wood ash to fluted pumpkin could assist farmers in achieving bumper harvest in the study area. Farmer in the study area should adopt the application of 4t/ha of wood ash to fluted pumpkin.